Design, synthesis and bioactivity evaluation of Galf mimics as antitubercular agents. (24th June 2016) - Liu, Chunyan; Hou, Linyu; Meng, Aiguo; Han, Gang; Zhang, Weiguo; Jiang, Shende
Graphical abstract: Abstract: A series of novel Gal f mimics has been synthesized and characterized by IR, 1 H NMR, 13 C NMR, mass spectral and element analysis. All the newly prepared compounds were screened for their antitubercular activities. Bioactivity assays manifested that most of Gal f mimics exhibited good antitubercular activities. Especially compound4d and4e displayed remarkable antitubercular efficacies, which were comparable to ethambutol.